Family Formation and Returning to Institutional Religion in Young Adulthood - Uecker, Jeremy E. (Journal for the scientific study of religion, 2016)
Institutional religious involvement wanes during young adulthood, but evidence suggests life-course factors such as family formation bring people back to religion. Using the National Longitudinal Study of Adolescent to Adult Health (Waves 1, 3, and 4), we examine how often young adults who were involved in institutional religion as adolescents returnmeasured by religious service attendance and religious affiliationafter leaving in emerging adulthood, and how this return is patterned by family formation. The majority of young adults who leave do not return to regular religious service attendance, regardless of their family formation. But single parents, married parents, and childless married individuals are more likely, and childless cohabiting couples less likely, to return to religious communities than those who are both single and childless. Only married parents are more likely than childless singles to reaffiliate, though there is marginal evidence that childless married adults may also be more likely. Thus, the institutions of religion and family are still linked, even though overall levels of religious return are not as high as expected.